2018
DOI: 10.1002/biot.201700688
|View full text |Cite
|
Sign up to set email alerts
|

Site‐Specific Photoconjugation of Beta‐Lactamase Fragments to Monoclonal Antibodies Enables Sensitive Analyte Detection via Split‐Enzyme Complementation

Abstract: Protein fragment complementation assays (PCA) rely on a proximity-driven reconstitution of a split reporter protein activity, typically via interaction between bait and prey units separately fused to the reporter protein halves. The PCA principle can also be formatted for use in immunossays for analyte detection, e.g., via the use of small immunoglobulin binding proteins (IgBp) as fusion partners to split-reporter protein fragments for conversion of pairs of antibodies into split-protein half-probes. However, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…This enabled analyte detection via split-enzyme complementation in a dual-antibody assay. 46 Perols et al used SPPS to introduce BPA or benzoylbenzoic acid (BBA, a benzophenone attached to a flexible linker) at positions 5 and 32 in Z, where Z32BPA could cross-link 41% of human IgG1 heavy chains and Z5BBA cross-linked 66% of mouse IgG1 heavy chains. 47 Further improving the cross-linking abilities of the Z domain, Hui et al reported up to 80% cross-linking of mouse IgG3 heavy chains by introducing BPA at position 17 in the protein domain and 47% conjugation efficiency for human IgG1 with BPA at position 35.…”
Section: Affinity Ligands and Their Role In Site-specific Conjugation Of Unmodified Antibodiesmentioning
confidence: 99%
“…This enabled analyte detection via split-enzyme complementation in a dual-antibody assay. 46 Perols et al used SPPS to introduce BPA or benzoylbenzoic acid (BBA, a benzophenone attached to a flexible linker) at positions 5 and 32 in Z, where Z32BPA could cross-link 41% of human IgG1 heavy chains and Z5BBA cross-linked 66% of mouse IgG1 heavy chains. 47 Further improving the cross-linking abilities of the Z domain, Hui et al reported up to 80% cross-linking of mouse IgG3 heavy chains by introducing BPA at position 17 in the protein domain and 47% conjugation efficiency for human IgG1 with BPA at position 35.…”
Section: Affinity Ligands and Their Role In Site-specific Conjugation Of Unmodified Antibodiesmentioning
confidence: 99%
“…The ability to easily utilize this vast source of “off-the-shelf” recognition elements within protein switches would improve the scope and uptake of the technology. Whole antibodies have only rarely been used for in vitro protein switches, but in the new commercially available Lumit immunoassay, antibodies are linked to each half of a proximity protein switch . Attachment is via chemical modification of the antibodies with synthetic ligands that bind a self-labeling protein tag (HaloTag) on the reporter fragments .…”
Section: Recognition Elementmentioning
confidence: 99%
“…They have thus been superseded by enzymatic reporters that enhance sensitivity by signal amplification, as in ELISAs. Despite enormous possibilities, the same set of reporter enzymes encompassing proteases, , β-lactamase, ,,, glucose dehydrogenase, ,,,, and luciferases , ,,,,,, are repeatedly used in protein switches, perhaps due to their history as reporters in other assays and the ease of recombinant production. Dependent on the enzyme and substrate, there are four key formats: colorimetric, fluorometric, luminescent, and electrochemical.…”
Section: Reportermentioning
confidence: 99%
See 2 more Smart Citations